Circulating Metabolomic Signature in Generalized Pustular Psoriasis Blunts Monocyte Hyperinflammation by Triggering Amino Acid Response - Yu, Ning; Peng, Chen; Chen, Wenjuan; Sun, Ziwen; Zheng, Jianfeng; Zhang, Shujie; Ding, Yangfeng; Shi, Yuling (Frontiers in Immunology, 2021)
Generalized pustular psoriasis (GPP), the most severe type of psoriasis, is characterized by dysregulated systemic inflammatory response. The cellular and molecular basis of GPP is poorly understood. Blood monocytes serve as the first line of host defense and producers of inflammatory cytokines including IL-1beta. How the immune response of monocytes is affected by metabolic internal environment in GPP remains unclear. To investigate this, we performed a metabolomic, functional, and mechanistic analysis of blood monocytes and GPP serum. We demonstrated a significant increase in IL-1beta production from GPP monocytes. In GPP circulation, serum amyloid A (SAA), an acute-phase protein, was dramatically upregulated, which induced the release of IL-1beta from monocytes in a NLRP3-dependent manner. Using metabolomic analysis, we showed that GPP serum exhibited an amino acid starvation signature, with glycine, histidine, asparagine, methionine, threonine, lysine, valine, isoleucine, tryptophan, tyrosine, alanine, proline, taurine and cystathionine being markedly downregulated. In functional assay, under amino acid starvation condition, SAA-stimulated mature IL-1beta secretion was suppressed. Mechanistically, at post-transcriptional level, amino acid starvation inhibited the SAA-induced NLRP3 inflammasome activation and reactive oxygen species (ROS) generation. Moreover, the immune-modulatory effect of amino acid starvation was blocked by silencing general control nonderepressible 2 kinase (GCN2), suggesting the involvement of amino acid response (AAR) pathway. Collectively, our results suggested that decreased serum amino acids in GPP blunted the innate immune response in blood monocytes through AAR pathway, serving as a feedback mechanism preventing excessive inflammation in GPP.